Comparing apples and manzanas: instrument development for cross-national analysis of emotional labour in public service jobs. (2018) - Yang, Seung-Bum; Guy, Mary E.; Azhar, Aisha; Hsieh, Chih-Wei; Lee, Hyun Jung; Lu, Xiaojun; Mastracci, Sharon
This paper contributes to research on emotional labour by offering a measurement instrument that is suitable for making comparisons across nations. We confront the challenge of measurement equivalence by reporting survey items that achieve configural and partial metric invariance across seven nations on four continents. Survey items for each of three emotional labour constructs - emotive capacity, deep acting, and surface acting (more accurately called pretending) - were developed by first analysing pilot data from a sample of nations. After variables were refined, full data collection was conducted by surveying public service workers in seven countries. Multi-group confirmatory factor analysis then tested for cross-national invariance. Results confirm both configural and partial metric invariance of the items, enabling comparison of emotional labour demands and its consequences across nations.